ภูมิปัญญาไทยกับการส่งเสริมการเรียนรู้และการสร้างอาชีพ Thai Local Wisdom and Their Role in Promoting Learning and Occupations - sungsri, sumalee - (Journal of Education Studies, Chulalongkorn University, 2014)
การวิจัยนี้มีจุดประสงค์เพื่อ 1) ศึกษาสภาพการถ่ายทอดความรู้และการส่งเสริมอาชีพของครูภูมิปัญญาไทย 2) ศึกษารูปแบบและกระบวนการเรียนรู้ที่เกิดขึ้นในศูนย์การเรียนรู้ภูมิปัญญาไทย 3) ศึกษาแนวทางส่งเสริมให้ครูภูมิปัญญาไทยร่วมส่งเสริมการเรียนรู้และการประกอบอาชีพของประชาชนในชุมชน กลุ่มตัวอย่างได้จากทุกภูมิภาคทั่วประเทศประกอบด้วย 1) ภูมิปัญญาไทยที่มีความเชี่ยวชาญใน 9 ด้าน จำนวน 36 คน 2) ครูการศึกษาในระบบ 216 คน 3) ครูการศึกษานอกระบบ 180 คน 4) ประชาชนผู้มารับบริการจากครูภูมิปัญญาไทย 360 คน และ 5) ผู้เชี่ยวชาญ 30 คน เครื่องมือวิจัยประกอบด้วย แบบสัมภาษณ์ครูภูมิปัญญาไทยและประชาชนผู้รับบริการ และแบบสอบถามครูการศึกษาในระบบและการศึกษานอกระบบ วิเคราะห์ข้อมูลโดยการหาความถี่ ค่าร้อยละ ค่าเฉลี่ย และการวิเคราะห์เนื้อหา ผลการวิจัยในประเด็นหลัก สรุปได้ดังนี้ 1) ครูภูมิปัญญาไทยทั้ง 9 ด้าน ได้มีส่วนส่งเสริมการเรียนรู้ทั้งการศึกษาในระบบ การศึกษานอกระบบและการศึกษาตามอัธยาศัย ได้แก่ การช่วยเป็นวิทยากร เป็นแหล่งศึกษาดูงาน ส่งเสริมการประกอบอาชีพได้แก่ ช่วยฝึกอบรมอาชีพและช่วยแนะนำการหารายได้เสริม 2) รูปแบบและกระบวนการเรียนรู้ที่เกิดขึ้นในศูนย์การเรียนรู้ภูมิปัญญาไทย มีหลายลักษณะ หลายวิธีการผสมผสานกันได้แก่ การอธิบาย สาธิต และ ฝึกปฏิบัติในสถานการณ์จริง 3) แนวทางเพื่อให้ครูภูมิปัญญาไทยได้ส่งเสริมการเรียนรู้ในระบบ การเรียนรู้นอกระบบ การเรียนรู้ตามอัธยาศัยได้แก่ กำหนดให้มีหลักสูตร กิจกรรมการเรียนการสอนและแหล่งเรียนรู้เกี่ยวกับภูมิปัญญาไทย และส่งเสริมการประกอบอาชีพของประชาชนโดยช่วยฝึกอบรมอาชีพในหลายด้าน เป็นแหล่งความรู้ด้านอาชีพ และเผยแพร่ความรู้ผ่านสื่อต่างๆ The objectives of this study were: 1) to study the present situation of learning and occupations promotion by Thai local wisdom; 2) to study formats and learning processes existed at the local wisdom learning centres; and 3) to propose guidelines for encouraging Thai local wisdom to participate in promoting learning and occupations of people in communities. The samples, who were drawn from every region of the country, included: 36 local wisdom in 9 aspects of expertise; 216 school teachers ; 180 non-formal education teachers ; 360 local people who obtained knowledge from the local wisdom; and 30 experts. Research instruments were the interview forms for the local wisdom and for rural people, questionnaires for local school teachers and for non-formal education teachers. The data were analyzed by frequency, percentages, means and content analysis. The main findings were: 1).The local wisdom in 9 aspects of expertise have promoted learning in the form of formal, non-formal and informal education such as being resource persons and their centres are the places for study visit. They also promoted occupations in various forms such as organizing vocational trainings and giving advises for income generating.; 2) The format and learning processes occurred were integrated in various forms such as lecturing, demonstrating, and practicing in the real situation.; 3).Guidelines proposed for encouraging the local wisdom to promote formal, non-formal and informal education were, for examples, assigning the curriculum, teaching and learning, and learning resources related to local wisdom. For promoting occupations were, for examples, organizing vocational trainings in various fields, being vocational resource centres, and disseminating vocational knowledge through various kinds of media.